2013
DOI: 10.1002/jcb.24422
|View full text |Cite
|
Sign up to set email alerts
|

Sodium valproate potentiates staurosporine‐induced apoptosis in neuroblastoma cells via Akt/survivin independently of HDAC inhibition

Abstract: Sodium valproate (VPA) has been recently identified as a selective class I histone deacetylase (HDAC) inhibitor and explored for its potential as an anti-cancer agent. The anti-cancer properties of VPA are generally attributed to its HDAC inhibitory activity indicating a clear overlap of these two actions, but the underlying mechanisms of its anti-tumor effects are not clearly elucidated. The present study aimed to delineate the molecular mechanism of VPA in potentiating cytotoxic effects of anti-cancer drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…This kind of approach has already been used with other HDACis to demonstrate the specificity of the anti-HDAC activity effect (20)(21)(22). Interestingly, both derivatives did not have any effect on cell growth or on CSC population ( Supplementary Fig.…”
Section: Histone Deacetylase Inhibitors Modulate Breast Cancer Stem Cmentioning
confidence: 93%
“…This kind of approach has already been used with other HDACis to demonstrate the specificity of the anti-HDAC activity effect (20)(21)(22). Interestingly, both derivatives did not have any effect on cell growth or on CSC population ( Supplementary Fig.…”
Section: Histone Deacetylase Inhibitors Modulate Breast Cancer Stem Cmentioning
confidence: 93%
“…Kramer and colleagues suggested that induction of cancer cell apoptosis with the treatment of HDACi such as VPA is driven by hyperacetylation of Stat1 that allow its interaction with NF-kB and reduces NF-kB signaling [191], thus suppressing expression of NF-kB target genes including Bcl-XL, survivin, and Stat5. A study shows that valpromide (VPM), an amide analog of VPA that does not inhibit HDAC also potentiates cell death in cancer cells associated with decreased level of survivin indicating an alternative mechanism of VPA-mediated apoptosis [192]. Farnesylthiosalicylic acid, a Ras inhibitor was tested in combination with VPA.…”
Section: Therapeutic Targeting Of Survivinmentioning
confidence: 99%
“…Multiple mechanisms have been proposed to explain the potent anticancer activity of HDAC inhibitors in neuroblastoma cells. For example, the effect of a HDAC inhibitor VPA on apoptosis was mediated by repression of survivin and Akt pathway [23]. In addition to histones, HDACs also target numerous non-histone proteins such as Ku70, p53 and HSP90 [24].…”
Section: Introductionmentioning
confidence: 99%